2002
DOI: 10.1088/0031-9155/48/1/306
|View full text |Cite
|
Sign up to set email alerts
|

Integral-transport-based deterministic brachytherapy dose calculations

Abstract: We developed a transport-equation-based deterministic algorithm for computing three-dimensional brachytherapy dose distributions.The deterministic algorithm has been based on the integral transport equation. The algorithm provided us with the capability of computing dose distributions for multiple isotropic point and/or volumetric sources in a homogenous/heterogeneous medium. The algorithm results have been benchmarked against the results from the literature and MCNP results for isotropic point sources and vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…Some other work based on the integral transport equation has been performed by Zhou and Inanc. [15][16][17] Some features of the algorithm used in this work are introduced in the following sections.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some other work based on the integral transport equation has been performed by Zhou and Inanc. [15][16][17] Some features of the algorithm used in this work are introduced in the following sections.…”
Section: Methodsmentioning
confidence: 99%
“…The details of the computational algorithm implemented for the photon transport can be found in a previous article. 17 One of the new additions not covered in those articles is the fluorescence radiation. In addition to the inclusion of this physical mechanism, we also redesigned the algorithm for parallel processing.…”
Section: A Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because these methods are all based on phasespace discretization, TG-186 categorizes them as grid-based Boltzmann equation solvers (GBBS). Zhou and Inanc developed a GBBS, which they applied to LE brachytherapy, 64 based on direct evaluation of the integral LBTE, expanded in orders of scattering. Daskalov et al applied a 2D discreteordinates GBBS (from DANTSYS) (Ref.…”
Section: Iib2 Deterministic Solutions To the Linear Boltzmann Tranmentioning
confidence: 99%
“…The RMS difference over the entire plane of comparison was 1.95%. Zhou et al have solved the LBTE for a single 6711 125 I seed 3 and an 81 seed implant 4 to study distortions induced by interseed and intraseed attenuation and reported results within Ϯ5% of Monte Carlo. Calculation time for the single seed case was approximately 42 min whereas the calculation time for the 81 seed case was 35 h on two processors.…”
Section: Introductionmentioning
confidence: 99%